On distinction of the reed species (Phragmites, Poaceae) according to the molecular phylogenetic data - N. N. Nosov; A. A. Gnutikov; E. O. Punina; E. M. Machs; G. Yu Konechnaya; A. V. Rodionov (Проблемы ботаники Южной Сибири и Монголии, 2020)
Molecular phylogenetic analysis of the marker sequences ITS and trnL–trnF of the Phragmites australis,P. altissimus, some putative hybrids between them and the sample of P. australis s. l. from Republic of Tuva was performed.ITS1 sequences of the sample from Tuva were studied by the New-generation sequencing method (NGS) revealingintragenomic polymorphism of the ITS sequences in allopolyploid species. We showed good differences betweenP. australis and P. altissimus in the ITS1-5.8S rDNA-ITS2 sequences by many single-nucleotide substitutions anddeletions, in particular, there is a 12 b.p. deletion. P. australis s. l. sample from Tuva (Hemchik river) demonstrates aseparate position on the phylogenetic tree. All reed species studied by us do not have significant differences between eachother according to the chloroplast sequences trnL–trnF.